Analisis Potensi Sumur dan Peramalan Keadaan Sumur Dimasa Depan Dengan Menggunakan Metode Wiggins pada Sumur FS-09ST Lapangan Sukowati - Faroucki Seven Mahendra; Hadziqul Abror (Journal of Sustainable Energy Development, 2023)
Production of the FS-09ST well began on January 17th, 2009 with oil production is 401 BOPD and peak production on May 13th, 2011 with oil production is 3254 BOPD. Over time, production has decreased until the well was shut-in on October 9th, 2020 with oil production is 11 BOPD due to the high watercut which reached 99.55%. The location of this research is administratively located in Campurejo Village, Bojonegoro District, Bojonegoro Regency. Analysis of well potential and well forecasting was carried out using the Wiggins method based on well test data conducted on November 10th, 2020. This method is used because the FS-09ST well has three-phase fluid and a high water cut. The results of the analysis show that the maximum flowrate is 3899.44 BFPD, the optimum flowrate is 2340 BFPD, and a recommended production flowrate is 2340 BFPD at flowing bottom hole pressure (Pwf) is 1240 Psi to avoid water coning. Based on forecasting future IPR, it is known that the economic limit rate of this well is when the reservoir pressure is 1965 Psi with a oil flowrate of 10.08 BOPD.